WISATA EDUKASI BERBASIS KEARIFAN LOKAL DI KAWASAN WISATA BATIK TRUSMI KOTA CIREBON - Sri Puspa Dewi, Roels Ni Made; Brenda Pingkan Vania, Fidelia (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
The area in Cirebon City that develops tourist destinations with local wisdom is the Trusmi Batik Tourism Area. This tourist area consists of several business actors who offer educational tours for tourists. The purpose of this study was to examine what educational tourism activities are found in tourist areas based on local wisdom. Data collection methods consist of literature study, observation, interviews, and documentation. Determination of informants interviewed using the social situation method consisting of places, actors, and activities with the number of informant 20 people. The data analysis method used was qualitative data analysis which was sorted based on data collection, data processing, and drawing conclusions. The results of this study are the form of local wisdom that exists in the Trusmi Batik Tourism Area is tangible local wisdom, namely batik, handicrafts, culinary, and souvenirs. The form of intangible local wisdom, namely in the form of values ??that are firmly held by the local community. Educational tourism developed include science education tours and cultural educational tours. Science Educational Tour in the form of learning about the history of batik and its philosophy. Cultural Education Tourism is related to knowledge about Wayang figures, and cultural festivals based on local resources, and culture and traditions regarding Topeng Cirebon.